PENERAPAN ASESMEN UNTUK MENGUKUR PERKEMBANGAN FISIK MOTORIK HALUS PADA ANAK USIA DINI - Alfarikhma Zuana Rachildaa; Nur Mawaddah (incrementapedia, 2022)
This article aims to describe the problems that exist in Sinar Mentari Kindergarten schools in the application of assessments to measure the physical development of fine motor skills in early childhood. The discussion of the article uses descriptive qualitative research methods. The results of the analysis describe the product produced in this study is an assessment to measure fine motor  physical development in early childhood. The collage applied at Sinar Mentari Godog Laren Lamongan Kindergarten is in the form of LKA (Children's Worksheet) with the theme of plants, sub-theme of flowers, which refers to the RPPH (Daily Learning Implementation Plan). With his shortcomings in conducting assessments, parents have not accepted the development of their children. As a parent, you want to be informed about the growth and development of your child. In addition to needing the results of child development, parents also want their children to grow and develop.